Aqueous, Alcoholic Treated and Proximate Analysis of Maydis stigma (Zea mays Hairs) - Wan Rosli, W. I.; Nurhanan, A. R.; Mohsin, S. S. J.; Farid, C. G. (Microscopy Society of Singapore, 2008)
Globally medicinal plants and herbs have long been commercially exploited and referred as traditional medicines of tangible value. This medicinal plant and herb is closely associated with local complementary alternative medicine. Sadly, many of this traditional natural available product of local plants are poorly elucidated or scientifically proven. With the advent of sophisticated techniques and new approach in high-resolution microscopy, this medicinal plant prowess can be revisited and harness. Of interest in this paper, is a local plant that was once quoted in the American National formulary for prostate problems. The longitudinal surface texture of the corn silk thread fibre was lamellated and non porous when intact protuberances were present. The silk thread sample was recorded the diameter ranging from 654 – 627 μm. When cut/section, the microtubules are present and gives the features of a thru and thru opening while some of them seems occluded. The surface of the thread looks smooth and clean of artifacts or microorganisms suggestive that ethanol acts a viable chemical fixative to corn silk presentation. Ethanol extracts contained 0.41% nitrogen compounds while water extract were at the richest source (1.40%) followed by fresh corn silk (0.18%).